1997
DOI: 10.1038/bjc.1997.395
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of thyroid cancer among Norwegian women married to fishery workers – a retrospective cohort study

Abstract: Summary The relationship between thyroid cancer in women and the occupation of their spouses was examined in a retrospective cohort study, with special reference to fishery. Of the 2.9 million women registered in the Central Population Registry of Norway on 31 December 1991, 1.2 million women had a spouse registered with an occupation in one or more of the censuses in 1960, 1970 or 1980. The women were assigned to ten broad categories based on the first digit of their husbands five-digit Nordic occupational cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
(14 reference statements)
1
9
0
1
Order By: Relevance
“…The risk increases by the number of fish-meals per week. The outcome is compatible with the results published in the study of the thyroid cancer risk of fishermen's wives, published in 1997 (19): In Norway spouses of fishery workers have a higher risk than women married to men of any other main occupational class. The results also suggest that the increased risk is restricted to the older birth cohorts of spouses while younger wives seem to have a risk closer to the population average.…”
Section: Studies and Meta-studies At The End Of A Centurysupporting
confidence: 81%
“…The risk increases by the number of fish-meals per week. The outcome is compatible with the results published in the study of the thyroid cancer risk of fishermen's wives, published in 1997 (19): In Norway spouses of fishery workers have a higher risk than women married to men of any other main occupational class. The results also suggest that the increased risk is restricted to the older birth cohorts of spouses while younger wives seem to have a risk closer to the population average.…”
Section: Studies and Meta-studies At The End Of A Centurysupporting
confidence: 81%
“…In contrast to overall incidence, the distribution of different histologic types of TC differs between IDA and ISA (2,8,23). Several case-control studies have shown that iodine deficiency leads to an increased relative proportion of FTC compared with areas of endemic goiter (12,24) (1996); Harrach and Williams (1995)) have reported a higher incidence of FTC ( 5/30 Á/40%), which may be more prominent in men, in iodine-deficient areas (10, 24 Á/26). Following the introduction of iodine supplementation in iodine-deficient regions, however, an increase in the relative proportion of PTC has been recorded, usually concurrent with a drop in frequency of the follicular and anaplastic types (13,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidence rates are reported in areas of high iodine intake (12); however, there is no general consensus on these findings (13). In fact, the overall incidence of differentiated thyroid carcinoma is not considered to be influenced by iodine intake in a population, whereas the distribution of the types of thyroid carcinoma seems to be related to the intake of iodine, with fewer of the more aggressive follicular and anaplastic carcinomas and more PTC (papillary thyroid carcinomas) being observed in iodine-rich areas.…”
mentioning
confidence: 99%
“…[22] The result of our study is in accordance with other recent studies on the incidence of thyroid carcinoma in Iran, showing a high rate of papillary carcinoma and a low rate of follicular carcinoma. [18] Previous studies have shown that the most prevalent histology in an endemic goiter region is follicular, [5,23] but if we consider that for ~12 years salt has been iodinized in this region, resulting in a decrease in the prevalence of thyroid goiter, [24] the increase in the incidence of papillary carcinoma can be explained. In addition, previous studies in Iran have shown that even before the salt iodinization process was initiated, papillary carcinoma was the most prevalent histology in Iran.…”
Section: Discussionmentioning
confidence: 99%